Syntheses and Nonlinear Optical (NLO) Properties of Ru(II) and Pt(II) - Acetylide Dendrimers - Alanazi, Hana Mohammed (Journal of natural sciences, life and applied sciences, 2020)
Organometallic dendrimers and its applications have been introduced. Bis((4-(phenylethynyl)phenyl)ethynyl)bis-(tributylphosphine)platinum(II) with dendritic acetonide end groups have been synthesised by the divergent method. 1,3,5-benzyl(4-ethynyl(phenylethynyl))-trans-[Ru(dppe)2]ethynyl-3,5-phenyl{4-ethynyl(phenylethynyl)-trans-[Ru(4-(phenylethynyl))(dppe)2]}2)3 with nine dialkynylruthenium centers have been synthesised by convergent method. Optical power limiting measurements performed at 532 nm show that the OPL properties improve with increasing size of the dendritic substituent. Z-scan measurements carried out at different pulse-repetition frequencies show that the two-photon absorption cross-section is 10 GM. Significant increase in NLO properties seen on generation increase is maintained when the coefficients are scaled by the number of metal atoms, the dendrimer molecular weights, or hyperpolarizability (π-delocalizable electrons) in the dendritic structures. Nonlinear optical (NLO) properties are required for various applications, including the processing of optical signals, optical data storage, nanophotonics, and biophotonics.
Keywords: organometallic; dendritic compound; nonlinear photoelectron; acetylide